THE DESCRIPTION OF RESILIENCE IN POST-ACUTE ATTACK PATIENT WITH CORONARY ARTERY DISEASE - Eva Puspawatie; Ayu Prawesti; Titin Sutini (Belitung Nursing Journal, 2018)
Background: Coronary heart disease patients shall experience physical, psychological and social changes that will affect life. The psychological condition of outpatients that has been investigated include anxiety, depression and quality of life, all of these problems can be attributed to resilience. Objective: The purpose of this study was to determine the image of resilience of coronary heart disease patient following up the acute attack in outpatient ward. Methods: The research method used quantitative descriptive using CD-RISC instrument 25. Instrument had validity value r = 0.83, P <.0001 and reliability value of Cronbach’s α 0.89. The selection of sample with consecutive sampling and got sample number 50 people for 2 weeks. Data were analyzed based on the value of each respondent categorized using tertile to see the overall resilience picture, while for the five sub-variables measured using the mean and standard deviation. Result: The results showed that almost half of respondents had 70-75 resilience. The mean value of sub-variables if sorted from the lowest to the highest is trust and reinforcement (2.71±0.58); competence and resilience (2.88±0.53); relationships with others (2.92±0.48); self-control (3.04±0.62) and spiritual influence (3.33±0.45). These results are influenced by lack of self-efficacy, optimism and family support. Conclusion: The conclusions of the research resilience of patients are in the medium category, for the lowest sub-variable value is trust and strengthening, while the highest is the spiritual influence. So, it is advisable to provide education to improve management skills post-acute attacks and increase social support in the care of patients at home.